The autonomic nervous system and the brainstem: A fundamental role or the background actors for consciousness generation? Hypothesis, evidence, and future directions for rehabilitation and theoretical approaches. Issue 1 (29th November 2019) - Sattin, Davide; Leonardi, Matilde; Picozzi, Mario
Abstract: Introduction: One of the hardest challenges of the third century is to develop theories that could joint different results for a global explanation of human consciousness. Some important theories have been proposed, trying to explain the emergence of consciousness as the result of different progressive changes in the elaboration of information during brain processing, giving particular attention to the thalamocortical system. Methods: In this article, a summary review of results that highlighted as cerebral cortex could not be so fundamental for consciousness generation is proposed. In detail, three topics were analyzed: (a) studies using experimental approach (manipulating stimuli or brain areas), such as decorticated animals or subliminal presentation of stimuli; (b) studies using anatomo‐clinical method (conscious inferenced from observed behaviors); and (c) data from neurostimulation of subcortical areas or of the autonomic nervous system. Results: We sketch two speculative hypothesis relative, firstly, to the possible independence from cortical areas of the on/off mechanism for consciousness generation and, secondly, to the possible role of information variability generated by the bottom‐up exchange of information among neural systems as a switch for consciousness. Conclusions: A broad range of evidence regarding the functional role of the brainstem and autonomic nervous system is reviewed for its bearing on a future hypothesis regarding the generation of consciousness experience. Abstract : The complex role of some extra‐cortex systems, like brainstem nuclei and autonomic nervous system, should be carefully studied for consciousness generation; Brainstem presents a complex architecture with a lot of nuclei and several long and fast ways of communication between body and brain; 3‐consciousness could be an on/off mechanism.